Disrupting times in the wake of the pandemic: Dispositional time attitudes, time perception and temporal focus. (February 2022) - Loose, Tianna; Wittmann, Marc; Vásquez-Echeverría, Alejandro
Introduction: The COVID-19 pandemic has majorly disrupted many aspects of people's lives, provoking psychosocial distress among students. People's positive and negative attitudes towards the past, present and future were a dispositional pre–COVID-19 reality. Faced with a pandemic, people have reported disruptions in the speed of passing time. People can shift their attention more towards the past, present or future when major changes in society occur. These aspects of psychological time would be key to understanding the quality of psychosocial adjustment to the pandemic. We hypothesized that dispositional time attitudes impact psychosocial distress because they would trigger situational changes in our time perception and temporal focus. Methods: One hundred and forty-four university students in Uruguay responded to self-report questionnaires online while in-person classes were cancelled. Students reported on shifts in temporal focus, changes in time awareness and dispositional time attitudes. Reactive psychological, social and learning environment distress were reported. Results: Students reported substantial changes in time perception and temporal focus. A correlation matrix showed significant relationships between time attitudes, focus and awareness. For example, psychological distress was correlated with negative time attitudes, slower passage of time, boredom, blurred sense of time and shifting focus to the past. Mediation models were derived. The indirect effect of time attitudes on psychological distress was significant through past focus. Discussion: Dispositional time attitudes would impact students' capacity to cope with the pandemic. Situational shifts in temporal focus and perception were prevalent and can be viewed as temporal coping mechanisms in the wake of powerful societal change. Our mediation models showed that those with negative time attitudes experienced more psychological distress because they shifted their attention to the past. Future directions for research and practical implications are discussed.